Effect of Self-Esteem and Parents’ Psychological Control on the Relationship Between Teacher Support and Chinese Migrant Children’s Academic Achievement: A Moderated Mediation - Liu, Guirong; Teng, Xiuqin; Zhu, Dongchun (Frontiers in Psychology, 2019)
Based on Self-Determination Theory (SDT)，this study attempted to examine the relationship between teacher support and migrant children’s academic achievement as well as the mediating role of self-esteem and the moderating role of psychological control. Six hundred and one migrant children participated in the study and completed self-report questionnaires concerning teacher support, self-esteem and psychological control. Results indicated that self-esteem mediated the positive relationship between teacher support and academic achievement. Psychological control moderated the relationship between teacher support and self-esteem. Furthermore, psychological control moderated the mediating effect of self-esteem on teacher support–academic achievement relationship, such that the mediating effect was weaker when the level of psychological control was high.